Self-disclosure individu androgini melalui instagram sebagai media eksistensi diri - Setiadi, Gabriella Jacqueline (Jurnal Studi Komunikasi, 2019)
People are divided into two characteristic, feminine and masculine. As the time goes by, people recognize the new gender which is androgyny. The evolution of androgyny can’t be separated from the role of social media, one of them is Instagram. Instagram is currently being used by androgynous individuals to do self-disclosure. One of the Androgynous individuals in Indonesia is Jovi Adhiguna Hunter who does self-disclosure on Instagram through lifestyle content. By using the self-disclosure theory by Joseph A. Devito, researchers focused on the self-disclosure dimension featured by Jovi Adhiguna Hunter. This research is a qualitative research using in-depth interview and non participant observation as data collection technique. Data analysis techniques used are Interactive Model Miles and Huberman. The result of this research stated that Jovi Adhiguna actively uses Instagram by using the insta stories feature and uploading photos and videos in feeds to do self-disclosure. He often shares positive content and is honest with his personality as an androgynous individual. Jovi is also close and friendly towards his followers so that he gets his existence as an androgynous individual.